Crustal anisotropy across northern Japan from receiver functions - Bianchi, I. (J Geophys Res Solid Earth, 2015)
Northern Japan is a tectonically active area, with the presence of several volcanoes, and with frequent earthquakes among which the destructive M (w) = 8.9–9.0 Tohoku‐oki occurred on 11 March 2011. Tectonic activity leaves an imprint on the crustal structures, on both the upper and the lower layers. To investigate the crust in northern Japan, we construct a receiver function data set using teleseismic events recorded at 58 seismic stations belonging to the Japanese National (Hi‐net) network. We isolate the signals, in the receiver function wavelet, that witness the presence of anisotropic structures at depth, with the aim of mapping the variation of anisotropy across the northern part of the island. This study focuses on the relation among anisotropy detected in the crust, stresses induced by plate convergence across the subduction zone, and the intrinsic characteristics of the rocks. Our results show how a simple velocity model with two anisotropic layers reproduces the observed data at the stations. We observe a negligible or small amount of signal related to anisotropy in the eastern part of the study area (i.e., the outer arc) for both upper and lower crust. Distinct anisotropic features are observed at the stations on the western part of the study area (i.e., the inner arc) for both upper and lower crust. The symmetry axes are mostly E‐W oriented. Deviation from the E‐W orientation is observed close to the volcanic areas, where the higher geothermal gradient might influence the deformation processes.